Decoding a Decade: Digital Forensic Law Evolution - Sonia, Citra; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of scholarly works related to digital forensic within the legal domain, spanning the years 2012 to 2022. The study began with a search on Lens.org, yielding a total of 11,376 scholarly works, which were subsequently filtered to focus exclusively on journal articles, reducing the dataset to 4,482. Further refinement narrowed it down to 3,802 works within the specified date range. The final filter for "law" as the subject matter resulted in 898 scholarly works. This data is now available on Zenodo in both CSV and BibTeX formats, facilitating research and literature reviews in the realm of digital forensics within the legal context. Analysis of the data reveals the most prolific publishers, active countries, top authors, and institutions. Notably, the study highlights that the United Kingdom is the most active country in the publication of digital forensic research, and it sheds light on the evolution of this field over the years, with 2021-2022 being the peak in scholarly output. "Digital Forensic Research Landscape" serves as a valuable resource for anyone seeking insights into the legal aspects of digital forensics and the dynamic landscape of related research. Highlights: Comprehensive Analysis: Examining 10 years of digital forensic research within the legal domain. Global Trends: Identifying the most active countries and institutions in this field, with a focus on the United Kingdom. Evolution of Scholarly Output: Highlighting the surge in digital forensic publications in 2021-2022. Keywords: Digital Forensic Research, Legal Perspective, Scholarly Analysis, Decade Review, Global Insights